‘Imagining ourselves’ as participating publics: an example from biodiversity conservation - Castro, P.; Mouro, C. (Public Understanding of Science, 2016)
This article examines how residents in Natura 2000 sites in Southern Portugal ‘imagine themselves’ as publics participating in biodiversity conservation. Through nine focus groups (n = 49) it seeks to understand whether and how these self-imaginations reproduce and/or resist experts’ highly shared, hegemonic, representations across two dimensions: the epistemic and the normative. Analysis of the groups’ discussions shows that (1) reproduction is clearer in the normative dimension, conveyed through discursive formats that place ‘people’ as its actor and exempt the Ego from it; (2) resistance is clearer in the epistemic dimension, relying on vibrant claims of local knowledge, yet it can be maintained as hidden discourse; (3) the forms of reproduction or resistance that emerged were hybrid ones; and (4) self-imaginations are more fragmented and negative in normative matters and more unified and positive in epistemic matters. We discuss how these findings help understand how hegemonic representations are maintained/resisted in enduring public–expert relations.